Molecular packing analysis of the crystal smectic E phase of a benzothieno-benzothiophene derivative by a combined experimental / computational approach. Issue 13 (21st October 2021) - Hofer, Sebastian; Bodlos, Wolfgang; Novák, Jiří; Sanzone, Alessandro; Beverina, Luca; Resel, Roland
ABSTRACT: The molecule 2-decyl-7-phenyl[1]benzothieno[3, 2-b][1]benzothiophene has gained a lot of attention since high charge carrier mobility was observed in thin film transistors. Its thermotropic liquid crystalline states may play an important role in the thin film formation since the smectic A and the crystal s mectic E phase (SmE) are claimed to be pre-stages of the final bulk structure. To understand the phase diversity, structural characterisation of solution processed thin films is performed by X-ray diffraction in the complete temperature range up to the isotropic state at 240°C. The diffraction pattern of the SmE phase is analysed in detail. Peak broadening analysis reveals that the crystallographic order across the smectic layers is larger than the order along the smectic layers. A combined experimental and computational approach is used to determine the molecular packing within the SmE phase. It leads to a number of different packing motifs. A comparison of the calculated diffraction pattern with the experimental results reveals that nano-segregation is present within the SmE phase. Energy consideration clearly favours a herringbone arrangement of the aromatic units. The nano-segregation within the SmE phase with herringbone packing of the aromatic units is accompanied with interdigitation of side chains from neighbouringherringbone layers. Graphical abstract: uf0001